Body composition of adult cystic fibrosis patients and control subjects as determined by densitometry, bioelectrical impedance, total-body electrical conductivity, skinfold measurements, and deuterium oxide dilution - Newby, MJ; Keim, NL; Brown, DL (The American journal of clinical nutrition, 1990)
This study contrasts body compositions (by six methods) of eight cystic fibrosis (CF) subjects with those of eight control subjects matched for age, height, and sex. CF subjects weighed 84% as much as control subjects. Densitometry and two bioelectrical impedance-analysis methods suggested that reduced CF weights were due to less lean tissue (10.7, 9.5, and 10.4 kg). Total-body electrical conductivity (TOBEC) and skinfold-thickness measurements indicated that CF subjects were leaner than control subjects and had less fat (5.4 and 3.6 kg) and less lean (5.2 and 7 kg) tissue. D2O dilution showed a pattern similar to TOBEC (8.3 kg less lean, 2.7 kg less fat tissue). Densitometry estimates of fat (mass and percent) were not correlated (r < 0.74, p > 0.05) with any other method for CF subjects but were correlated with all other methods for control subjects. CF subjects contained less fat and lean tissue than did control subjects. Densitometry by underwater weighing is unsuitable for assessing body composition of CF patients.